PNPLA3-Ile148Met and TM6SF2-Glu167Lys increase susceptibility to metabolic dysfunction-associated steatotic liver disease in children - Yao, Hengpan; Xia, Zhiyi; Liu, Yijing; Dong, MengJun; Yang, Kairui; Zhou, Fang (Frontiers in Endocrinology, 2025)
BackgroundWith the rising global prevalence of childhood obesity, the incidence of metabolic dysfunction-associated steatotic liver disease (MASLD) in pediatric and adolescent populations is also increasing. The genetic mechanisms underlying MASLD remain incompletely elucidated. This study aimed to investigate the roles of eight genetic loci—PNPLA3-Ile148Met, PNPLA3-Lys434Glu, GCKR-Leu446Pro, TM6SF2-Glu167Lys, LEPR-Lys109Arg, LEPR-Lys656Asn, IRS1-Gly971Arg, and KLB-Arg728Gln—in the susceptibility to MASLD in Chinese children and adolescents, in order to provide scientific evidence for genetic research on MASLD. We hypothesized that PNPLA3-Ile148Met and TM6SF2-Glu167Lys variants confer susceptibility to MASLD in children.MethodsA total of 350 children and adolescents aged 7–17 years were enrolled, including 196 with MASLD (case group) and 154 healthy controls. Demographics, medical history, anthropometric measurements, and hepatic B-ultrasound data were collected. Fasting morning blood samples were obtained for biochemical analysis and genotyping. Statistical analyses included chi-square tests, Fisher’s exact tests, and multivariate logistic regression to identify predictive factors for pediatric MASLD.ResultsThe allele frequencies of PNPLA3-Ile148Met, PNPLA3-Lys434Glu, and TM6SF2-Glu167Lys were significantly higher in the MASLD group than in the control group (PNPLA3-Ile148Met and TM6SF2-Glu167Lys: both P_FDR < 0.001; PNPLA3-Lys434Glu: P_FDR=0.024), indicating an association with increased MASLD risk. In contrast, the allele frequencies of GCKR-Leu446Pro and LEPR-Lys109Arg were significantly lower in the MASLD group (P_FDR=0.009), suggesting potential protective effects. Multivariate logistic regression identified male sex, the PNPLA3-Ile148Met-GG genotype, and the TM6SF2-Glu167Lys-CT genotype as independent risk factors for MASLD. Additionally, carriers of the PNPLA3 rs738409 GG genotype exhibited significantly higher levels of AST, ALT, and TC compared to those with the GC genotype (all P_FDR < 0.001).ConclusionThe PNPLA3-Ile148Met and TM6SF2-Glu167Lys gene polymorphisms are independent risk factors that significantly increase the risk of MASLD in Chinese children. Additionally, the PNPLA3-Lys434Glu variant is associated with increased risk at the allele level. In contrast, GCKR-Leu446Pro and LEPR-Lys109Arg may confer protective effects. This study provides new evidence for genetic susceptibility to MASLD in the pediatric population.